Being a dynamic teacher of second language: endorsing location-specific, classroom oriented innovative practices of post-method condition - Hensman, C.A. (University of Jaffna, 2018)
Number of methods and approaches are being introduced into the field of second language teaching. Though these various methods signify distinct perspectives of teaching, no single method proved itself to be ideal for a particular context. None of the methods can be realized in their purest form in the actual classroom primarily because they are not derived from classroom experience and experimentation. The top-down approach which is often employed in the invention of teaching methods proves futile as the practitioners are not being consulted and considered in the process of creating new methods and approaches to teaching. It is always the theorizers who are at the centre and the practitioners occupy the disempowered periphery of the power circle. This needs to be revised and a power shift might bring in desired results. Kumaravadivelu’s “Beyond methods” endorses this power shifts and uplifts the position of a teacher. In a post method framework, the hands of the teacher are not tied to a particular system. Whatever she feels appropriate for a particular group of students can be adopted and utilized in the classroom. The fundamentals of Post method framework rely on paying attention to the socio psycho considerations of a given particular context and endorses location-specific, classroom oriented innovative practices. The current study is an experimental one and examines the suitability of post-method pedagogy in a Sri Lankan context. A classroom intervention was carried out to secure the necessary data. The research findings suggested that the application of post-method pedagogy is beneficial in learning English as a Second Language. The results also highlighted that the application of post method condition enhanced learner-autonomy, student engagement and student performance.
Keywords: Beyond-method; Dynamic; Innovation; post-method; practitioners